The Impact of an Educational Program Based on Interaction between Knowledge Journeys through Web Quest and the Environment of Constructional Education on Acquiring Problem-Solving Skills among Third-Grade Students in Saudi Arabia - Al Qahtani, Nasser Ayed (Dirasat: Educational Sciences, 2020)
The aim of this study is to identify the impact of an educational program based on the interaction between knowledge journeys through Web Quest and the learning environment on acquiring problem-solving skills among average third grade students in Saudi Arabia. The study is based on a quasi-experimental method. A sample of (38) students was selected. They were randomly divided into two groups: an experimental group and a control group. The study was used as a measure of problem solving skills. The honesty and consistency coefficients of the instrument were carried out. The results of the study showed that there was a statistically significant effect at the level of α (00.05) of the educational program based on the interaction between cognitive trips across Web Quest and bilding education environment on acquiring problem-solving skills among third grade students in Saudi Arabia.